Application of Cluster Analysis for Polymer Classification According to Mechanical Properties - Pezer, Danijela (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
The selection of the appropriate polymer material represents one phase in the product design, both, in terms of data on the different properties of the material and for detailed assessments and selection of the best material for the selected product. In the material selection phase, it is necessary to define criteria related to the mechanical properties of the material (strength, stiffness, toughness). Another important item is certainly the stress-strain diagram by which the materials can be classified into certain groups, based on their mechanical properties. The paper presents a study of materials classification according to the following groups: Hard and brittle, Hard and strong, Hard and tough and Soft and tough materials, using the cluster analysis (k-means algorithm).